Scheduling algorithm of data sampling times in the integrated communication and control systems - Hong, Seung Ho (IEEE transactions on control systems technology, 1995)
Integrated communication and control systems (ICCS) consist of several distributed control processes which share a network medium. Performance of several feedback control loops in the ICCS is subject to the network-induced delays from sensor to controller and from controller to actuator. The network-induced delays are directly dependent upon the data sampling times of the control components which share a network medium. In this study, a scheduling algorithm of determining data sampling times is developed using the window concept, where the sampled data from the control components in the ICCS share a limited number of windows, so that the performance requirement of each control loop is satisfied as well as the utilization of network resources is considerably increased. The scheduling algorithm is verified by discrete-event/continuous-time simulation model of an example of ICCS.< >